2019
DOI: 10.17263/jlls.631552
|View full text |Cite
|
Sign up to set email alerts
|

A technological pedagogical content knowledge (TPACK) sssessment of pre-service EFL teachers learning to teach English as a foreign language

Abstract: The aim of the present paper is to measure the technological pedagogical content knowledge (TPACK) of preservice EFL teachers learning to teach English as a foreign language (EFL). In order to collect data, a survey, designed and validated by Başer et al. (2016), was used. The survey consists of five sections which are technological knowledge (TK), content knowledge (CK), pedagogical knowledge (PK), pedagogical content knowledge (PCK) and a fifth section that combines technological content knowledge (TCK), tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
7
28
0
4
Order By: Relevance
“…It is also similar to the results of some studies done around the word like: (Sarıçoban, Tosuncuoğlu, & Kırmızı, 2019), (Chai, Koh, & Tsai, 2013), and (Alghamdi, 2017). The most crucial point that should be noticed is that the current study differs from all previous studies in its community and the place where it was applied though it may resemble it to some extent in the results.…”
Section: The Third Question Of the Studysupporting
confidence: 89%
See 4 more Smart Citations
“…It is also similar to the results of some studies done around the word like: (Sarıçoban, Tosuncuoğlu, & Kırmızı, 2019), (Chai, Koh, & Tsai, 2013), and (Alghamdi, 2017). The most crucial point that should be noticed is that the current study differs from all previous studies in its community and the place where it was applied though it may resemble it to some extent in the results.…”
Section: The Third Question Of the Studysupporting
confidence: 89%
“…These results showed that the degree of content knowledge (CK) of Saudi EFL teachers in Madinah city is high. This degree is almost like what the study of (Sarıçoban, Tosuncuoğlu, & Kırmızı, 2019) indicated in its results. It differed from the result gained from the study (Chen & Goh, 2014) that was on a medium degree.…”
Section: First Questionsupporting
confidence: 82%
See 3 more Smart Citations